Efficient In Vitro Full‐Sense‐Codons Protein Synthesis. Issue 10 (8th June 2022) - Wu, Yang; Tang, Mengtong; Wang, Zhaoguan; Yang, Youhui; Li, Zhong; Liang, Shurui; Yin, Peng; Qi, Hao
Abstract: Termination of translation is essential but hinders applications of genetic code engineering, e.g., unnatural amino acids incorporation and codon randomization mediated saturation mutagenesis. Here, for the first time, it is demonstrated that E. coli Pth and ArfB together play an efficient translation termination without codon preference in the absence of class‐I release factors. By degradation of the targeted protein, both essential and alternative termination types of machinery are completely removed to disable codon‐dependent termination in cell extract. Moreover, a total of 153 engineered tRNAs are screened for efficient all stop‐codons decoding to construct a codon‐dependent termination defect in vitro protein synthesis with all 64 sense‐codons, iPSSC. Finally, this full sense genetic code achieves significant improvement in the incorporation of distinct unnatural amino acids at up to 12 positions and synthesis of protein encoding consecutive NNN codons. By decoding all information in nucleotides to amino acids, iPSSC may hold great potential in building artificial protein synthesis beyond the cell. Abstract : Global translation termination is identified and completely removed with deletion of one set of essential factors, RF1, RF2, SsrA, ArfA, ArfB, and Pth, to achieve in vitro protein synthesis with 64 sense codons (iPSSC), which is capable of transferring all information in nucleotide to amino acids. iPSSC builds a versatile platform with all‐sense genetic code for artificial protein engineering.